HUBUNGAN KECERDASAN EMOSIONAL DENGAN BURNOUT SYNDROME PADA MAHASISWA YANG MENJALANI PEMBELAJARAN DARING - Widayana, I Gede Angga Ariesta; Suarningsih, Ni Kadek Ayu; Utami, Kadek Cahya (Coping: Community of Publishing in Nursing; Vol 10 No 2 (2022): April 2022, 2022)
Changes in the online learning system have potential to cause burnout syndrome. This study aimed to investigate the correlation between emotional intelligent with burnout syndrome among student in Faculty of Medicine, Udayana University who ware ongoing in online learning. This research is quantitative research with descriptive correlative. The research design used is cross sectional. Sample on this study were 243 sample selected through proportionate stratified random sampling. Collecting data using Trait Emotional Intelligence Questionnaire - Adolescent Short Form and Maslach Burnout Inventory-Student Survey. Data analysis using Spearman Rank test. The results showed that there is negative and weak correlation between emotional intelligent with burnout syndrome. It means that the higher of emotional intelligence will decrease the burnout syndrome and otherwise.